Pengaruh pelatihan âOrangtua SADARâ Terhadap peningkatan psychological well-being pada orangtua yang memiliki anak remaja - , Luh Mea Tegawati; , Prof. Dr. Sofia Retnowati ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Parenting for adolescents is affected by the condition of parentsâ psychological well-being (PWB). This study applied training for parents of adolescent children. Orangtua SADAR (Sayang dan Reflektif) training program used mindful parenting to improve psychological well-being of parents. PWB was measured using Ryff's Scales of Psychological Well-Being (RPWB) which was consisted of 23 items with alpha reliability score of 0,806. Criteria of participants in this study were parents (both father and mother or only one of them) who had adolescent children and were willing to participate in the training, had medium PWB condition which is marked with the presence of all or one of characteristics as followed: not quite able to accept their present condition, had negative relationship with other people, werenât assured in their childrenâs capability, didnât have purpose in life, personal development were hampered, were unable to control their own environment, whose parents were high school graduates, lived in Daerah Istimewa Yogyakarta. There were 8 participants assigned to experiment group and 5 participants assigned to control group. Method used in this study was quasi experimental method which was untreated control group design with dependent pretest and posttest samples. The training program was consisted of 12 training sessions and 1 follow up session. Quantitative data was analyzed using non parametric Mann Whitney Test (U test). Qualitative data consisted of results from observation, interview, and diary analysis were also presented. The gain scores of experiment and control group showed that there were significant difference with U score = -2,304 with p = 0,021 (p<0,05).